COVIVA: Effect of transcutaneous auricular vagal nerve stimulation on fatigue-syndrome in patients with Long Covid – A placebo-controlled pilot study protocol - Mortimer Gierthmuehlen; Petra Christine Gierthmuehlen (PLoS ONE, 2025)
Background: Up to 80% of patients who develop coronavirus disease-2019 (Covid-19) infection subsequently experience long covid/post-covid syndrome. The World Health Organization (WHO) has estimated that >770 million patients have been infected with Covid-19 globally. Even if only 10% of these patients develop long covid, > 75 million patients will suffer for a long period. Among the various symptoms of post-covid syndrome, fatigue is common, affecting up to 60% of the patients. As observed in other viral infections, elevated levels of inflammatory cytokines may play a role. Transcutaneous auricular vagal nerve stimulation (taVNS) is a noninvasive method that modulates the immune system via the central nervous system and has shown promising effects in autoimmune diseases and improving fatigue. In this pilot study, we investigated the feasibility of daily taVNS in patients with long covid-related fatigue. Additionally, the effects of taVNS on fatigue and quality of life will be analyzed. Methods: A total of 45 adult patients with long covid associated fatigue syndrome will be enrolled in this study, and will be randomized to the above-threshold-stimulation, below-threshold-stimulation, or sham-stimulation arms, after being informed that they will feel the stimulation. The above-threshold-group will receive a 4-week-long left-sided cymba conchae taVNS with 25 Hz, 250 µs pulse width 28s/32s on/off paradigm for 4 h throughout the day. The below-threshold group will receive stimulation below the sensational threshold, whereas the sham group will receive no stimulation following application of a non-functional electrode. The daily stimulation protocol will be recorded either manually or using the provided app. Three well-established questionnaires, the Multidimensional-Fatigue-Inventory-20, Short-Form-36, and Beck-Depression-Inventory, and the newly established Post-Covid-Syndrome-Score will be completed both before and after 4 weeks of stimulation. Discussion: The primary endpoint has been set as the patients’ average daily stimulation time after 4 weeks, while secondary endpoints include the effects of taVNS on fatigue and Quality of Live (QoL). As a non-invasive treatment option, taVNS may be a notable alternative for patients with post-covid related fatigue. Trial registration: This study was approved by the local ethics committee (23/7798) and registered (DRKS00031974) (see supporting information files). Ethics & Dissemination: The ethical justifiability of this study was supported by prior research demonstrating the safety of taVNS. Patients will be recruited by general practitioners, and written informed consent will be obtained. All data will be pseudonymized for collection and storage. The study results will be published in peer-reviewed journals with the aim of providing evidence of the potential of taVNS in long covid management. The study will be conducted in accordance with the principles of the Declaration of Helsinki.